A propeller-shaped μ4-carbonate hexanuclear dysprosium complex with a high energetic barrier to magnetisation relaxation. Issue 42 (6th October 2016) - Holmberg, Rebecca J.; Kuo, Che-Jung; Gabidullin, Bulat; Wang, Chia-Wei; Clérac, Rodolphe; Murugesu, Muralee; Lin, Po-Heng
Abstract : A Dy6 complex composed of two Dy3 triangular units was isolated and found to exhibit slow relaxation of the magnetisation under zero applied dc field, resulting in a high energetic barrier to relaxation. Abstract : A Dy6 complex composed of two Dy3 triangular units, [Dy6 (μ3 -OH)(CO3 )3 (bsc)3 (MeOH)14 (H2 O)](Cl)5 ·(H2 O)·(MeOH)2 (1 ), was isolated and found to exhibit slow relaxation of the magnetisation under zero applied dc field, resulting in a high energetic barrier to relaxation.